Intercultural Articulation and the Production of Symbolic Capital: The Cheng Yu Column in Indonesian Media Discourse - Widhiandono, Doan; Subiakto, Henri; Sugihartati, Rahma (representamen, 2026)
This study examines how the Cheng Yu column in Harian Disway operates as an arena for the production of symbolic capital through the intercultural articulation of Chinese cultural values in representing Indonesian public figures. Drawing on Pierre Bourdieu’s theory of symbolic capital, intercultural communication theory, and Norman Fairclough’s critical discourse analysis, the research investigates both institutional strategy and discursive practice behind the column’s production. The analysis is based primarily on qualitative data obtained through an in-depth interview with the newspaper’s Chief Executive Officer, complemented by a close reading of selected column texts. The findings demonstrate that the column functions not merely as a cultural literacy feature but as a structured mechanism of symbolic production within the media field. By associating classical Chinese idioms (cheng yu) with contemporary political leaders, corporate figures, and cultural personalities, the column symbolically elevates these individuals through culturally loaded moral narratives. In this process, traditional Chinese philosophical values—such as wisdom, perseverance, and ethical leadership—are strategically mobilized to frame public figures within a discourse of virtue and prestige. Furthermore, the study finds that the symbolic capital generated through such intercultural representation is not purely cultural. It is convertible into relational and economic capital through strengthened networks, audience engagement, and brand differentiation in a competitive media market. The column thus illustrates how cultural knowledge can be strategically deployed as a resource in media institutions. By situating the Cheng Yu column within the broader dynamics of symbolic exchange, this study contributes to media and intercultural communication scholarship. It conceptualizes the media not only as a channel of information but also as a field of symbolic governance where cultural narratives, institutional interests, and market considerations intersect. Keywords: symbolic capital; intercultural communication; Bourdieu